2022
DOI: 10.1136/bjo-2022-321511
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and clinical landscape ofARR3-associated MYP26: the most common cause of Mendelian early-onset high myopia with a unique inheritance

Abstract: AimsTo elucidate genetic background of early-onset high myopia (eoHM) and characteristics of ARR3-associated MYP26.MethodsVariants in 14 genes reported to contribute to eoHM, including ARR3, were selected from exome sequencing data set and classified into different categories following American College of Medical Genetics and Genomics guidelines based on in silico prediction, associated phenotypes, confirmation and cosegregation analysis. The available clinical data of individuals were summarised.ResultsPathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Variants in the ARR3 gene have been linked to X-linked female-limited eoHM, which is a rare disorder predominantly affecting females and exhibiting a femalelimited inheritance pattern [2,[5][6][7]. Similar inheritance patterns have been observed in cases of epilepsy and cognitive impairment associated with variants in the PCDH19 gene [8].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Variants in the ARR3 gene have been linked to X-linked female-limited eoHM, which is a rare disorder predominantly affecting females and exhibiting a femalelimited inheritance pattern [2,[5][6][7]. Similar inheritance patterns have been observed in cases of epilepsy and cognitive impairment associated with variants in the PCDH19 gene [8].…”
Section: Introductionmentioning
confidence: 98%
“…Both genetic and environmental factors contribute to the development of eoHM. While environmental factors such as excessive reading or computer use, lack of outdoor activities, and insu cient lighting can contribute to myopia development [4], genetic factors are considered to be the primary drivers of eoHM [5].…”
Section: Introductionmentioning
confidence: 99%
“…The partial splicing-effect haplotype (LVAVA) in the L-M hybrid gene lead to eoHM with colorblindness due to changes in spectral sensitivity. In combination with our previous analysis, OPN1LW was found not only to be the top two most frequently implicated genes for nonsyndromic monogenic eoHM (2.4%), second only to ARR3 (3.1%), 18 but might be among the top five common causative genes for syndromic monogenic eoHM when patients with colorblindness were included. This is the first time that such unique haplotypes in a well-known gene have been implicated as one of the most common causes of nonsyndromic eoHM.…”
Section: Discussionsupporting
confidence: 68%
“… 15 , 17 One of our recent studies suggested that LVAVA haplotypes in OPN1LW may be the second most common cause of eoHM after ARR3 . 18 …”
mentioning
confidence: 99%
“…Variants in these genes can only explain about 6% of eoHM. 20 Except for these, eoHM may present as a key sign for other ocular or systemic diseases, and variants in genes responsible for such diseases contribute to about one-fourth of eoHM. 21,22 Therefore, the exact genetic defects for most high myopia are awaited to be discovered.…”
Section: Introductionmentioning
confidence: 99%